The compressibility of fill subjected to applied stress and inundation - R. Alrowaimi, Mohamed Muftah (2006)
Cut and fill in construction is inevitable in order to achieve the desired formation level for a structure. Structures maybe constructed on compacted fill provided it is compacted according to the requirement specification. However, for poorly compacted soil the settlements of foundation can be caused by consolidation of compressible fill under foundation loading, consolidation of the fill under its own weight, consolidation of the natural ground beneath the fill and the collapse settlement due to inundation. This project is concerned with the settlement of foundation not only due to the increment in the applied stress but also the compressibility due to inundation of water. A series of consolidation tests has been conducted on lateritic clay samples, prepared at various densities representing the poorly, well-compacted density and at maximum dry density. It was observed in this study that the collapse potential for UTM high plasticity Lateritic clay might cause moderate trouble or trouble for the foundation on poorly or non-compacted soil. While the main settlement was occurred due to the increment in the applied stresses. However, the collapse potential increases with the decrement in the moisture content which reflects reduction in the dry density of the soil. The collapse potential also shows an increase trend as applied stress increases